2014
DOI: 10.1111/1556-4029.12625
|View full text |Cite
|
Sign up to set email alerts
|

Emotional Intelligence and Criminal Behavior

Abstract: A large body of research links criminality to cognitive intelligence and personality traits. This study examined the link between emotional intelligence (EI) and criminal behavior. One hundred Egyptian adult male offenders who have been sentenced for theft, drug dealing or murder and 100 nonoffenders were administered the Bar-On Emotional Quotient Inventory (EQ-i). The offenders had lower levels of EI than the nonoffenders. In addition, EI varied as a function of the types of offenses. Namely, it decreased in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
12
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 30 publications
3
12
0
Order By: Relevance
“…In this sense, significant results were only found with respect to perceived emotional repair, which was actually lower in cases of high CPV and higher in cases of low CPV. These results were consistent with those reported in studies associating lower EI with CPV [61,62], as well as with research relating high EI scores to greater hostility, aggression and crime [45][46][47][48][49][50]. However, the findings reported here contrast with those described in studies that associated high EI with criminal behavior [51][52][53].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In this sense, significant results were only found with respect to perceived emotional repair, which was actually lower in cases of high CPV and higher in cases of low CPV. These results were consistent with those reported in studies associating lower EI with CPV [61,62], as well as with research relating high EI scores to greater hostility, aggression and crime [45][46][47][48][49][50]. However, the findings reported here contrast with those described in studies that associated high EI with criminal behavior [51][52][53].…”
Section: Discussionsupporting
confidence: 91%
“…Studies in which EI is associated with violence in adolescents have reported conflicting results. Most research concludes that high levels of EI are related to better adjustment, less hostility and aggression [46,47], as well as less participation in criminal behavior [45,48,49]. It has been confirmed that, after training adolescents in EI, they learn to properly manage their emotions and significantly reduce the use of aggressive strategies to resolve interpersonal conflicts [50].…”
Section: Ei and Cpvmentioning
confidence: 98%
“…Broad explanations of why violence occurs and who commits violent acts are provided by psychodynamic (e.g., Ogilvie, Newman, Todd, & Peck, 2014), biological (e.g., Tiihonen et al, 2014), sociological (e.g., Agnew, 2005), and social-psychological (e.g., Topitzes, Mersky, & Reynolds, 2012) perspectives. Researchers are, however, increasingly interested in the role of emotion and emotional expression in violent offending (see, e.g., Megreya, 2015), and a better understanding of these factors should inform specific interventions for people who commit inter-personal violence.…”
Section: Introductionmentioning
confidence: 99%
“…It was also found that the ones with lower IQ exhibited the highest levels of cognitive and behavioural impulsivity, and compared with higher IQ serious delinquents, low IQ serious delinquents were exposed to more risk factors, such as low academic achievement, being old for grade, depressed mood and Introduction "Don't become a mere recorder of facts, but try to penetrate the mystery of their origin" (Ivan Pavlov as cited in Alcorn, poor housing [10,11]. This encompasses emotional intelligence as well which has been seen to be significantly lower in people who have committed a crime [12,13]. In the Indian context, criminal behavior has been associated with higher scores on intelligence, impulsivity, suspiciousness, self-sufficiency and lower scores in emotional stability in those with a criminal record than average population [14].…”
Section: Resultsmentioning
confidence: 99%